Manual Testicular Detorsion under Propofol Sedation - Martyn Harvey; Giles Chanwai; Grant Cave (Case Reports in Medicine)
Acute spermatic cord torsion is a urologic emergency requiring accurate diagnosis and timely intervention to effect testicular salvage. We report a case of adolescent testicular torsion successfully reduced following manual detorsion under sedation at the Emergency Department. Scrotal exploration and bilateral orchidopexy were subsequently performed as a semielective procedure.